The Impact of Global Warming on Earth's Ecosystems and Future Sustainability - Felixa Graciela (Global Writing Academica Researching and Publishing, 2023)
Global warming, driven primarily by human-induced activities, has emerged as a pressing concern in recent decades. This paper presents a comprehensive analysis of the effects of global warming on Earth's ecosystems and the potential implications for future sustainability. The rise in greenhouse gas emissions, particularly carbon dioxide, has led to a significant increase in global temperatures, resulting in far-reaching consequences for biodiversity, weather patterns, and sea levels. This study highlights the urgent need for collaborative efforts to mitigate the effects of global warming and transition towards a more sustainable future.